(untitled) (The South East European Journal of Economics and Business, 2018)
This paper examines whether or not feedback trading strategies are present in the Athens (ASE) and Cyprus Stock Exchanges (CSE). The analysis employs two econometric models: the feedback trading strategy model, introduced by Sentana and Wadhwani (1992), and the exponential autoregressive model, proposed by LeBaron (1992). These two theoretical frameworks, separately, were joined with the FIGARCH (1, d, 1) approach. Both models assume two different groups of traders – the “rational” investors that build their portfolio by following the firms’ fundamentals and the “noise” speculators that ignore stock fundamentals and focus on a positive (negative) feedback trading strategy. The empirical results revealed that negative feedback trading strategies exist in the two underlying stock markets.